2016
DOI: 10.1093/alcalc/agw006
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Alcohol Sports Sponsorship and Consumption: A Systematic Review

Abstract: AimConcerns have been raised about the impact of alcohol sports sponsorship on harmful consumption, with some countries banning this practice or considering a ban. We review evidence on the relationship between exposure to alcohol sports sponsorship and alcohol consumption.MethodsSearch of electronic databases (PubMed, Cochrane Library, Google Scholar and International Alcohol Information Database) supplemented by hand searches of references and conference proceedings to locate studies providing data on the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 18 publications
4
59
1
Order By: Relevance
“…bars). We defined the ‘alcohol industry’ as any company that produces, markets or distributes alcoholic beverages (Brown, 2016). Thus, we excluded studies that focused upon aspects of alcohol availability (such as server behaviour, parental supply of alcohol) or policy-level intervention (such as minimum age laws, restrictions on hours, days and volumes of alcohol sales in a given community) not driven by industry.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…bars). We defined the ‘alcohol industry’ as any company that produces, markets or distributes alcoholic beverages (Brown, 2016). Thus, we excluded studies that focused upon aspects of alcohol availability (such as server behaviour, parental supply of alcohol) or policy-level intervention (such as minimum age laws, restrictions on hours, days and volumes of alcohol sales in a given community) not driven by industry.…”
Section: Methodsmentioning
confidence: 99%
“…Four further systematic reviews have considered marketing influences, including placement and availability (Meier et al ., 2008; Bryden et al ., 2012), price (Meier et al ., 2008), advertising (Meier et al ., 2008; Bryden et al ., 2012; Stautz et al ., 2016) and sports sponsorship (Brown, 2016) on alcohol consumption. Meanwhile, a recent systematic review has investigated the content of, and exposure to, alcohol marketing in relation to self-regulated guidelines (Noel et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, interest in this area has grown since 2009 (Belt et al, ; O'Brien et al, ; Wilcox et al, ), coinciding with an increase in sponsorship as a marketing tool. Studies have shown a direct relationship between exposure to sponsorship, brand awareness, and attitudes toward consumption (Brown, ; Davies, ), suggesting that greater exposure involves a greater intention to consume. Others have shown that the effects are nonsignificant (Davies, ).…”
Section: The Dilemma Of the Effectiveness Of Alcohol Brand Sponsorshipmentioning
confidence: 99%
“…In other countries (e.g., New Zealand), industry regulation and self‐regulation support the elimination of alcohol advertising at recreational activities and sporting events, restricting content, or imposing full bans (Chambers et al, ). The recent academic literature (Brown, ; Chambers et al, ) and international regulations pay special attention to sports sponsorship. Given the socioeconomic connotations of consuming alcohol, the literature recommends expanding knowledge, methodologies, and valid, reliable measures to assess, analyze, and compare the effectiveness of sponsorship by alcohol brands (Grohs, ).…”
Section: Introductionmentioning
confidence: 99%
“…Youth and young adults are further exposed to alcohol marketing through sponsorship of sports teams and events (Macniven 2015). Authors of a systematic review found positive associations between exposure to alcohol sports sponsorship and increased levels of consumption, including two studies reporting significant associations between exposure to sports sponsorship and increased levels of consumption among children (Brown 2016). Alcohol sponsorship of music festivals is another potential medium of exposure for young people and has the potential to increase level of brand recall, brand awareness and attitude towards the brand (Rowley 2008).…”
Section: Introductionmentioning
confidence: 99%